The Primacy of Regime Survival State Fragility and Economic Destruction in Zimbabwe - Simpson, Mark (Springer International Publishing, 2018)
This book analyses the past and ongoing decline of Zimbabwe under the rule of ZANU-PF, with a primary focus on the period 1997 to the present. In contrast to much existing literature on post-independence Zimbabwe which has focused on the political dimensions of Zimbabwe's fragility, this research highlights the economic aspects of Zimbabwe's regression flowing from prolonged mismanagement of the economy which has served to consolidate the rule of the country's political and economic elite. The Zimbabwean experience offers unique insights into the economic mensions of regime preservation. This book situates the Zimbabwe experience within the context of wider debates within the field of development studies, and the international community's response to such situations.